Parafunctional masseter muscle activity during waking is related to periodontitis progression: A pilot prospective cohort study. (17th February 2021) - Ekuni, Daisuke; Kato, Seiya; Kawakami, Shigehisa; Maruyama, Takayuki; Kataoka, Kota; Uchida‐Fukuhara, Yoko; Fukuhara, Daiki; Toyama, Naoki; Yokoi, Aya; Islam, Md Monirul; Khair, Subrina Binta; Kodama, Naoki; et al.
Abstract: Aim: The purpose of this pilot prospective cohort study was to investigate the effects of parafunctional masseter muscle activity on periodontitis progression among patients receiving supporting periodontal therapy (SPT). Materials and methods: We collected data of patients treated at Okayama University Hospital from August 2014 to September 2018. The progression group was defined as patients with ≥2 teeth demonstrating a longitudinal loss of proximal attachment of ≥3 mm during the 3‐year study period and/or at least one tooth extraction due to periodontitis progression. Surface electromyography of masseter muscles at baseline was continuously recorded while patients were awake and asleep. Results: We analysed 48 patients (36 females) aged 66.8 ± 9.1 years (mean ± SD). The rate of parafunctional masseter muscle activity during waking hours and sleeping hours at baseline was 60.4% and 52.1%, respectively. Cox's proportional hazards regression model showed that the incidence of periodontitis progression was significantly associated with number of teeth present ( p = 0.001) and parafunctional masseter muscle activity during waking hours ( p = 0.041). Conclusion: Our results suggest that parafunctional masseter muscle activity during waking hours is a risk factor for periodontitis progression among patients receiving SPT.